2021
DOI: 10.1126/science.abc3483
|View full text |Cite
|
Sign up to set email alerts
|

Imaging translation dynamics in live embryos reveals spatial heterogeneities

Abstract: Much is known about the factors involved in the translation of mRNA into protein; however, this multi-step process has not been imaged in living multicellular organisms. Here, we deploy the SunTag method to visualize and quantify the timing, location, and kinetics of the translation of single mRNAs in living Drosophila embryos. By focusing on the translation of the conserved major epithelial-mesenchymal transition (EMT)-inducing transcription factor Twist, we identified spatial heterogeneity in mRNA translatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 58 publications
5
62
0
Order By: Relevance
“…2 D). The uniform activation of twi transcription is also corroborated by a recent study that followed live accumulation of Twi and identified an early (within ∼5 min) and even appearance of Twi throughout the mesoderm during NC 14 ( Dufourt et al, 2021 ). The rapid activation of twi expression by Dorsal could be facilitated by the presence of multiple binding sites for the Zelda (Zld) pioneer factor, which clears the regulatory region from nucleosomes ( Sun et al, 2015 ) ( …”
Section: Resultssupporting
confidence: 76%
“…2 D). The uniform activation of twi transcription is also corroborated by a recent study that followed live accumulation of Twi and identified an early (within ∼5 min) and even appearance of Twi throughout the mesoderm during NC 14 ( Dufourt et al, 2021 ). The rapid activation of twi expression by Dorsal could be facilitated by the presence of multiple binding sites for the Zelda (Zld) pioneer factor, which clears the regulatory region from nucleosomes ( Sun et al, 2015 ) ( …”
Section: Resultssupporting
confidence: 76%
“…The snail-primary-enhancer_MS2 transgene was obtained by amplification of the sna endogenous promoter and primary enhancer using the primers listed in Supplementary Data 1 . The 128XMS2 tag 78 was inserted immediately upstream of the yellow reporter gene sequence of the pbphi-yellow plasmid 17 . The transgenic construct was inserted in the VK0033 landing site (BL9750) using PhiC31 targeted insertion 79 .…”
Section: Methodsmentioning
confidence: 99%
“…Several transcriptional factors, such as Slug, Twist, and ZEB1, have been reported to play a vital function in EMT (Kurppa et al, 2020;Dufourt et al, 2021;Huang et al, 2021). Slug is one of the critical regulators which lead to EMT and is closely related to cancer metastasis.…”
Section: Proposed Model Of Ppa1 In Breast Cancer Progressionmentioning
confidence: 99%